Semantic Analysis of Conceptual Metaphors in “New Heavens, New Earth, and New Jerusalem” in the Bible - Jane Saudila; I Gusti Nyoman Kamayana (EUNOIA Jurnal Teologi dan Pendidikan Agama Kristen, 2026)
This study aims to identify the categories of conceptual metaphors and analyze the meanings of metaphorical expressions found in the phrases “New Heavens,” “New Earth,” and “New Jerusalem” in the NIV (New International Version) Bible. The data source of this research consists of Bible verses containing these phrases collected from the website biblestudytools.com. This study applies the conceptual metaphor theory proposed by George Lakoff and Mark Johnson (1980) within the framework of cognitive semantics. The research uses a descriptive qualitative method. The data were collected through document analysis and note-taking techniques, while the analysis was conducted using textual analysis. The findings reveal that there are 10 conceptual metaphors identified from 7 Bible verses, consisting of 2 orientational metaphors, 7 ontological metaphors, and 1 structural metaphor. Furthermore, the study analyzes the meanings of the metaphorical expressions based on these categories. The results show that the metaphorical expressions in the selected verses convey deeper meanings related to transformation, renewal, and spiritual hope within the theological context of the Bible. Therefore, this study contributes to the understanding of conceptual metaphors in biblical texts and expands semantic studies in the field of cognitive linguistics.